ỨNG DỤNG TƯ DUY HỆ THỐNG TRONG PHÁT TRIỂN CÁC KHU DỰ TRỮ SINH QUYỂN THẾ GIỚI TẠI VIỆT NAM - Trí, Nguyễn Hoàng (Nhà xuất bản Nông nghiệp, 2016)
This presents a new approach of system thinking to be applied in practices of establishing and managing 8 biosphere reserves in Vietnam. With direction of “System thinking - Landscape planning - Inter-sectoral coordination - Quality economy”, all of Vietnam’s biosphere reserves are directly coordinated by People’s Committees of provinces or cities. This creates relevant conditions for carrying out activities regarding intersectoral and multi-disciplinary issues, but there are a lot of difficulties and challenges in the mechanisms of scrotal coordination and administrative management at present. The report also introduces UNESCO titles and their promotion for socio-economic value through activities of “Conservation for Development and Development for Conservation”. Lessons learnt from international and domestic experiences are introduced to facilitate analysis, implement and enhance the effectiveness of management in each of Vietnam’s biosphere reserves.